Colorimetric Biosensors Based on Polymer/Gold Hybrid Nanoparticles: Topological Effects of the Polymer Coating - Wang, Ruosong; Schirmer, Lucas; Wieduwilt, Torsten; Forster, Ronny; Schmidt, Markus A.; Freudenberg, Uwe; Werner, Carsten; Fery, Andreas; Rossner, Christian (Langmuir, 2022)
Gold nanoparticles decorated with analyte recognition units can form the basis of colorimetric (bio)sensors. The presentation of those recognition units may play a critical role in determining sensor sensitivity. Herein, we use a model system to investigate the effect of the architecture of a polymeric linker that connects gold nanoparticles with the recognition units. Our results show that the number of the latter that can be adsorbed during the assembly of the colorimetric sensors depends on the linker topology. We also show that this may lead to substantial differences in colorimetric sensor performance, particularly in situations in which the interactions with the analyte are comparably weak. Finally, we discuss design principles for efficient colorimetric sensor materials based on our findings.
CRIS-Team Scopus Importer:2023-03-20